PENGARUH KEMAMPUAN, PENGALAMAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN - Eza Herlambang Taufik; Muhammad Harlie; Kurniaty Kurniaty (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2017)
The evolution of the forex market is divided into two stages. World War IPeriod and the Bretton Woods period is included Fixed Rate Periodstage. At this stage, forex does not excite transactions because of exchange rate changes can only occur in a relatively narrow range. After a period of Bretton Woods, after the failure of Period Exchange Rates Remain in maintaining economic stability, forex transactions getting psyched. This occurs because the assessment of the exchange rate between countries be left entirely to the market mechanism. The market will determine whether the exchange rate is too expensive (over-valued) or too low (under-valued).This study aims to determine the effect of ability, experience and discipline together and partially on the performance forex trader in South Kalimantan. This type of research is quantitative method. The samples were obtained 56 votes. To determine the effect the ability, experience and discipline to the performance of the test statistic methods trader used multiple linear regression. Data processing was performed using IBM SPSS Statistics 23 program for Windows.Based on the results of the research show that together the ability, experience and discipline significant effect on the performance of forex traders in South Kalimantan. Partially, ability, experience and discipline positive and significant impact on the performance of forex traders in South Kalimantan.Keywords: Capability, Experience, Discipline and Performance